A simplified design procedure of parabolic trough solar field for industrial heating applications - Masood, R. (Asian Research Publishing Network, 2016)
This paper presents a stepwise approach for designing a Parabolic Trough Solar Collector system, which is the fastest growing technology amongst concentrated solar power technologies. This technology is mainly being used for electricity generation by steam power cycles, but there is huge potential for this technology to be used in industrial heating applications. Though this technology is already developed and successfully been used in many developed countries, but there is barely any development in Malaysia. The performance of parabolic trough collector system is highly dependent on geographic location and meteorological conditions. A parabolic trough solar heating system has been designed and simulated using meteorological data of Ipoh, Malaysia. Thermal performance of the designed system was evaluated for fixed load and without thermal energy storage. A unique set of conditions is required for designing the PTC system but the solar radiation and incident angle changes throughout the year. So, setting appropriate design point conditions is crucial in designing of PTC system. The effect of field size on capacity factor and dumped energy is also explained, using the concept of solar multiple. It was noted that increase in field size have very little impact on capacity factor for solar multiple values higher than 2. This study was conducted for solar-only system without thermal energy storage which resulted low annual capacity factor. So, it is not worth depending solely on solar energy, combination of solar with conventional fuel system can significantly contribute in reduction of fuel usage also the addition of thermal energy storage can add to its value even more. Â© 2006-2016 Asian Research Publishing Network (ARPN).